New Insights on Fak and Fak Inhibitors - Brullo, Chiara; Tasso, Bruno (Current Medicinal Chemistry, 2021)
Background: Focal adhesion kinase (Fak) is a cytoplasmic protein tyrosine kinase overexpressed and activated in different solid cancers; it has shown an important role in metastasis formation, cell migration, invasion and angiogenesis and consequently it has been proposed as a potential target in cancer therapy, particularly in a metastatic phase. In recent years, different investigations have highlighted the importance of new Fak inhibitors as potential anti-cancer drugs, but other studies evidenced its role in different pathologies related to the cardiac function or viral infection. Methods: An extensive bibliographic research (104 references) has been done concerning the structure of Fak, its importance in tumor development, but also in other pathologies currently under study. The compounds currently subjected to clinical studies were therefore treated using the appropriate databases. Finally, the main chemical scaffolds currently under preclinical investigation were analyzed, focusing on their molecular structures and on the activity structure relationships (SAR). Results: At the moment, only a few reversible ATP-competitive inhibitors are under investigation in pre-clinical studies and clinical trials. Other compounds, with different chemical scaffolds, are investigated to obtain more active and selective Fak inhibitors. This mini-review is a summary of different Fak functions in cancer and other pathologies; the compounds today in clinical trials and the recent chemical scaffolds (also included in patents) giving the most interesting results are investigated. In addition, PROTAC molecules are reported. Conclusion: All reported results evidenced that additional studies are necessary to design and synthesize new selective and more active compounds, although promising information has been obtained from associations between Fak inhibitors and other different anti- cancer drugs. In addition, the other important roles evidenced, both at the nuclear level and in non-cancerous cells, make this protein an increasingly important target in pharmaceutical chemistry.
Keywords: cancer therapy